The Phenomenon of Cyberbullying Behavior among Teenagers in Padang City: Preliminary Study - Nasuha Yazu Hannako; Melly Latifah; Yulina Eva Riany (Green Publisher Indonesia, 2024)
The phenomenon of cyberbullying is still something that continues to be discussed considering that the cases that occur are increasing every year. Currently, cyberbullying cases that occur among adolescents are of particular concern to many communities. It is feared that this can damage the developmental process in adolescents, especially with regard to their self-formation process. In Indonesia, research on cyberbullying has begun to develop, especially in big cities. Therefore, it is important to research the phenomenon of cyberbullying in other regions, one of which is Padang City. It is hoped that there will be a richness of information about the phenomenon of cyberbullying in Indonesia. The results showed that almost ¾ of the respondents knew the phenomenon of cyberbullying and about 22 percent of respondents had committed cyberbullying and less than 20 percent had been victims of cyberbullying. A more comprehensive study as well as interventions from the government and families are suggestions for this study. More research results will be explained in the discussion section.